재생입구 직접증발냉각기 적용이 제습냉방시스템 성능에 미치는 영향 - 다쉬 울찌우타스; 성상철; 오명도; 이대영 (대한설비공학회, 2010)
The purpose of this study is to make an analysis of influence on the cooling capacity and COP of a desiccant cooling system with a regenerative evaporative cooler when a direct evaporative cooler was applied to the inlet of regeneration process of this system. We used cycle simulation in order to analyze the performance of this system. From the cycle simulation, we knew that the optimal rotation time of desiccant rotor was between 160s and 220s and hardly ever affected cooling capacity of desiccant cooling system when this system was operated at the outdoor air condition of 35℃ and 40% RH and low regeneration temperature of 60℃. Also there was optimal area ratio of regeneration to dehumidification between 0.7 and 1.0. Our results showed that it had a small effect on the system’s cooling capacity to install direct evaporative cooler at the inlet of regeneration process.